Galectin-9 in cancer therapy: from immune checkpoint ligand to promising therapeutic target - Zhang, Minpu; Liu, Cun; Li, Ye; Li, Huayao; Zhang, Wenfeng; Liu, Jingyang; Wang, Liquan; Sun, Changgang (Frontiers in Cell and Developmental Biology, 2024)
Galectin-9 (Gal-9) is a vital member of the galectin family, functioning as a multi-subtype galactose lectin with diverse biological roles. Recent research has revealed that Gal-9’s interaction with tumors is an independent factor that influences tumor progression. Furthermore, Gal-9 in the immune microenvironment cross-talks with tumor-associated immune cells, informing the clarification of Gal-9’s identity as an immune checkpoint. A thorough investigation into Gal-9’s role in various cancer types and its interaction with the immune microenvironment could yield novel strategies for subsequent targeted immunotherapy. This review focuses on the latest advances in understanding the direct and indirect cross-talk between Gal-9 and hematologic malignancies, in addition to solid tumors. In addition, we discuss the prospects of Gal-9 in tumor immunotherapy, including its cross-talk with the ligand TIM-3 and its potential in immune-combination therapy.